2015
DOI: 10.3390/ma8041568
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Bi2O2Se with Ag Addition

Abstract: Polycrystalline Bi2O2Se/Ag nanocomposites were synthesized by spark plasma sintering process. Their thermoelectric properties were evaluated from 300 to 673 K. With the addition of silver, the conductive second phase Ag2Se and Ag can be observed, which results in a significant enhancement of electrical conductivity. The maximum conductivity is 691.8 S cm−1 for Bi2O2Se/20 vol.% Ag, which increased nearly 500 higher times than the pure Bi2O2Se bulk. ZT value can be enhanced greatly, ~0.07, for Bi2O2Se/5 vol.% Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Nevertheless, the electrical conductivity for pristine Bi 2 O 2 Se is too low for a high‐performance TE material (~2 S/cm). Previous studies concentrated on the replacement of part of Bi 3+ with tetravalent Sn 4+ , Bi deficiencies, as well as compositing with Ag to optimize the electrical transport properties. However, the relatively low ZT values of Bi 2 O 2 Se‐based materials should be further improved.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, the electrical conductivity for pristine Bi 2 O 2 Se is too low for a high‐performance TE material (~2 S/cm). Previous studies concentrated on the replacement of part of Bi 3+ with tetravalent Sn 4+ , Bi deficiencies, as well as compositing with Ag to optimize the electrical transport properties. However, the relatively low ZT values of Bi 2 O 2 Se‐based materials should be further improved.…”
Section: Introductionsupporting
confidence: 72%
“…Benefitting from both the improvement of the power factor and the suppression of the thermal conductivity, the maximum ZT value of 0.23 at 823 K is achieved for Bi 2 O 2 Se 0.985 Cl 0.015 , which is 188% higher than that of the pristine Bi 2 O 2 Se. Moreover, this figure of merit is higher than that of any other Bi 2 O 2 Se reported in the literature …”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the highest figure of merit ZT reaches 0.28 at 823 K for Bi 2 O 2 Se 0.96 Te 0.04 , which is enhanced by almost a factor of 2 as compared to that of the pristine Bi 2 O 2 Se. Figure B compares the ZT values of Bi 2 O 2 Se 0.96 Te 0.04 and those of other Bi 2 O 2 Se‐based thermoelectric materials, which shows that the thermoelectric performance of Te‐substituted Bi 2 O 2 Se is superior to those of previously reported works.…”
Section: Resultsmentioning
confidence: 78%
“…The temperature‐dependent ZT values for Bi 2 O 2 Se 1‐ x T e x ceramics (A); the comparison of ZT values of Bi 2 O 2 Se 0.96 Te 0.04 and those of other Bi 2 O 2 Se‐based thermoelectric materials (B) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…First, Bi 2 O 2 Se was suggested to be a good thermoelectric material. [2][3][4][5][6][7] In 2010, Ruleova et al reported the thermoelectric properties of Bi 2 O 2 Se and they found that Bi 2 O 2 Se is an n-type semiconductor with a very low thermal conductivity and a relatively high gure of merit ZT about 0.2 at 800 K. 2 Several theoretical works were also conducted to explore its thermoelectric properties. [8][9][10][11] Second, Bi 2 O 2 Se has an ultrahigh electron mobility.…”
Section: Introductionmentioning
confidence: 99%